Simulation Study on the Influence of Fire Partition on Curtain Wall Temperature in Super High-Rise Buildings in China. (1st July 2021) - Zhang, Tongtong; Cao, Di
Abstract : The poor fire resistance characteristic of super high-rise curtain wall makes the curtain wall design one of the main approaches to improve its capacity for prevention and control over fire and smoke spread. The propagation of smoke leads to the increase in the temperature of the curtain wall on the upper and lower floors of the fire floor and consequently leads to glass fracture and other serious consequences. Current codes have control over fire resistance performance and size of fire partition materials but do not include requirements on the position of curtain walls on floors. By changing the position of fire partition in curtain walls, the paper carries out three comparative simulation experiments on two forms of fire partition: spandrel and fire prevention cornice. Besides, PyroSim is used to calculate the comparative simulation of fire and smoke spread and obtain the data on temperature variation nephogram and monitoring points in the center line of glass curtain walls during different fire scenarios, so as to discuss the influence of different positions of spandrels and fire canopy on fire hazard and smoke. This study finds out the following: fire canopy can better prevent the longitudinal spread of fire smoke than spandrels. The fire canopy above spandrels can reduce the flue-gas temperature. The higher the spandrels above floors, the faster the temperature of the central lines of glass curtain walls above fire floors reduced. However, the higher the spandrels above floors, the more uneven the distributions of high-temperature regions and low-temperature regions, thus leading to the increase in horizontal temperature differences of glass panels. This research conclusion can be taken as a reference for fire protection design of super high-rise glass curtain wall.